Bridging Gaps in Breast Cancer Screening: A Comparative Study of Mexican Women in U.S. Rural and Urban Areas - Venera Bekteshi; Mario Schootman (SAGE Publishing, 2024)
Background: This study investigates breast cancer screening disparities among Mexican immigrant women in rural and urban U.S. communities, focusing on cultural beliefs, healthcare access, and geographical differences. Methods: A cross-sectional study of 350 Mexican immigrant women aged 40+ without prior cancer diagnosis was conducted in rural (<2000 population) and urban parts of the U.S. in 2015. Culturally tailored surveys during household visits, clinic appointments, and community meetings assessed cultural beliefs, mammography engagement, and family support. Comparative analyses t -tests and chi-square tests were conducted, with significance set at P  < .05. Results: Rural women demonstrated higher adherence to spiritualismo ( M  = 4.31, SD = 1.13) compared to their urban counterparts ( M  = 3.91, SD = 1.36), marianismo ( M  = 3.33, SD = 0.45 vs M  = 3.21, SD = 0.48), and machismo ( M  = 3.02, SD = 0.52 vs M  = 2.80, SD = 0.61). The rural women also reported higher mammography rates (54.4% vs 45.6%), with 60.4% undergoing four or more mammograms. Despite barriers such as doctor non-recommendation (55.0% rural vs 45.0% urban) and embarrassment (67.9% rural vs 32.1% urban), rural women engaged more in family discussions about cancer screenings (61.7% vs 38.3%) and received more family assistance in finding health information (59.8% vs 40.2%). Conclusions: This study elucidates significant rural-urban disparities in cultural adherence and family support among Mexican immigrant women, underscoring the necessity for culturally tailored interventions to enhance breast cancer screening rates and health outcomes.